A coupled plasticity-damage model of K418 nickel-based superalloy with pressure and temperature dependence. (June 2022) - Li, Bin; Cui, Yi; Liu, Shuo; Huang, Rining; Fu, Yan; Ding, Zhanming
Highlights: The pressure and temperature have large effect on plastic behavior of K418 nickel-based superalloy; A coupled plasticity-damage model considering pressure and temperature and is developed; The coupled plasticity-damage model can predict the plasticity and failure of K418 nikel-base superalloy well. The location of failure initiation, fracture pattern have showed close correspondence to the experimental results. Abstract: The issue of containment stems from the aero-engine field, and there is little research in the turbocharger field. In order to reduce the number of tests, development cycle and cost, it is necessary to predict the burst speed of the turbine accurately. In response to this problem, a coupled plasticity-damage model is developed for turbine materials according to the stress state and operating temperature of the turbine. The effect of stress triaxiality, temperature are considered in the plastic constitutive and the failure criterion. The stress update algorithm of plasticity-damage model is given. According to the operating temperature and stress state of the turbine, the experimental scheme of K418 nikel-base superalloy is designed to calibrate the plasticity-damage model. Finally, the coupled plasticity-damage model is verified by the specimens with the notch radius R 6 at 550 °C and 600 °C. The results show that the maximum error of proposed model is about 7.3%, which is better than the 14.2% prediction error of the constitutive model without any corrections. Moreover, the failure displacement can be predicted by the proposed constitutive model (the maximum error is about 8.2%), which is beyond the ability of traditional model. The location of failure initiation, fracture pattern in numerical studies have also showed close correspondence to the experimental results.